Circulating miR-192 is a prognostic marker in patients with ischemic cardiomyopathy. (July 2018) - Klenke, Stefanie; Eul, Sebastian; Peters, Jürgen; Neumann, Till; Adamzik, Michael; Frey, Ulrich H
Ischemic cardiomyopathy (ICM) is characterized by accumulation of p53 causing apoptosis of cardiomyocytes and resulting in upregulation of miRNA (miR)-192, which plays an important role in the development of heart failure after acute myocardial infarction. However, for other cardiomyopathies, miR-192 seems to have minor relevance. We tested in a prospective, observational study comprising 91 patients with diagnosed heart failure (59.3% ICM and 40.7% non-ICM), the hypothesis that miR-192 expression predicts survival in patients with ICM. Median follow-up was 59 months (range: 1–118). While miR-192 expression was significantly associated with age (p = 0.028), log-rank analysis revealed significant association with survival in ICM (p = 0.003) but not in non-ICM (p = 0.6). In ICM, median age at time of death was 84 years in patients with low miR-192 expression but 67 years with high miR-192 expression. Thus, miR-192 expression is associated with survival in ICM and represents a prognostic marker in ischemic heart failure.